Pharyngo‐Esophageal Modulatory Swallow Responses to Bolus Volume and Viscosity Across Time. (20th December 2021) - Nollet, Joeke L.; Cajander, Per; Ferris, Lara F.; Ramjith, Jordache; Omari, Taher I.; Savilampi, Johanna
Abstract : Objectives/Hypothesis: Modulation of the pharyngeal swallow to bolus volume and viscosity is important for safe swallowing and is commonly studied using high‐resolution pharyngeal manometry (HRPM). Use of unidirectional pressure sensor technology may, however, introduce variability in swallow measures and a fixed bolus administration protocol may induce time and order effects. We aimed to overcome these limitations and to investigate the effect of time by repeating randomized measurements using circumferential pressure sensor technology. Study Design: Sub‐set analysis of data from the placebo arm of a randomized, repeated measures trial. Methods: HRPM with impedance was recorded using a solid‐state catheter with 36 circumferential pressure sensors and 18 impedance segments straddling from hypopharynx to stomach. Testing included triplicates of 5, 10, and 20 ml thin liquid and 10 ml thick liquid boluses, the order of the thin liquid boluses was randomized. The swallow challenges were repeated approximately 10 minutes after finishing the baseline measurement. Results: We included 19 healthy adults (10/9 male/female; age 24.5 ± 4.1 year). Intrabolus pressure, all upper esophageal sphincter (UES) opening and relaxation metrics, and flow timing metrics increased with larger volumes. A thicker viscosity decreased UES relaxation time, UES basal pressure, and flow timing metrics, whereas UES opening extent increased. Pre‐swallow UES basal pressure and post‐swallow UES contractile integral decreased over time. Conclusion: Using circumferential pressure sensor technology, the effects of volume and viscosity were largely consistent with previous reports. UES contractile pressures reduced over time. The growing body of literature offers a benchmark for recognizing aberrant pharyngo‐esophageal motor responses. Level of Evidence: 3 Laryngoscope, 132:1817–1824, 2022